2007
DOI: 10.24036/ld.v1i1.7350
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Fungsi Tekstual Dalam Surat Kabar Harian “Haluan”

Abstract: This study is aimed at applying Haliday ' Key Words/phrases: text, textual function, news paper, editorial, theme A. PENDAHULUANTajuk rencana atau yang disebut dengan istilah "editorial" merupakan bagian yang memiliki peran penting dalam suatu surat kabar. Editorial mengandung misi pesan yang terdapat dalam suatu surat kabar. Editorial juga mencakup pendapat ataupun komentar dari redaktur tentang kejadian-kejadian yang telah, sedang atau akan berlangsung. Sebagaimana yang dinyatakan oleh Reah (2002:45) "Edito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…Generally, the first part of the text does not contain emotional statements because it serves as the introduction to what the rest of the text is about. This is in line with Rosa (2007a) arguing that unmarked themes are usually used in the text containing supportive statements. The unmarked themes show the ordinary order of a clause containing the 'participant^process' order.…”
Section: The Frequent Component Of Themes In the Orientation Of The Hikayat Deli Textsupporting
confidence: 84%
See 2 more Smart Citations
“…Generally, the first part of the text does not contain emotional statements because it serves as the introduction to what the rest of the text is about. This is in line with Rosa (2007a) arguing that unmarked themes are usually used in the text containing supportive statements. The unmarked themes show the ordinary order of a clause containing the 'participant^process' order.…”
Section: The Frequent Component Of Themes In the Orientation Of The Hikayat Deli Textsupporting
confidence: 84%
“…The choice of unmarked and marked themes also has several consequences. Rosa (2007a) found that an unmarked theme is usually to indicate the writer's agreement with certain issues, while a marked theme tends to be used to show the writer's disagreement.…”
Section: Kinds Of Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…The important role of clause theme in writing a text has attracted a number of researchers to conduct studies on theme-rheme organization in a text, such as theme-rheme pattern (Belmonte & McCabe-Hidalgo, 1998;Dejica-Cartis & Cozma, 2013;Ebrahimi, 2016;Jingxia & Li, 2013), theme markedness (Rosa, 2007a;Sofyan & Tarigan, 2018), and thematic progression (Gunawan & Aziza, 2017;He & Tian, 2018;Rahmawati, 2016;Rosa, 2007bRosa, , 2011Yang, 2008;Yunita, 2018). Those studies are particularly aimed at showing the contribution of theme-rheme patterns to the text cohesiveness due to several common problems related to textual cohesion and coherence in writing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, those previous studies seek to characterize ideas organization in certain text types. Some of them focused on ideas organization in exposition texts (Rosa, 2007a(Rosa, , 2007b, recount texts (Rahmawati, 2016;Yunita, 2018), explanation texts (Yang, 2008), and news item texts (Sofyan & Tarigan, 2018). The results of their studies successfully formulate typical characteristics of theme and thematic progression pattern in particular text types.…”
Section: Introductionmentioning
confidence: 99%